Extracting past atmospheric warming and urban heating effects from borehole temperature profiles. (November 2016) - Bayer, Peter; Rivera, Jaime A.; Schweizer, Daniel; Schärli, Ulrich; Blum, Philipp; Rybach, Ladislaus
Highlights: Land use changes are included in analytical inversion of borehole temperatures. At four sites the contribution from buildings and asphalt could be backtracked. Urban structures tend to cause higher ground heat flux than atmospheric warming. Abstract: Borehole temperature logs in urban areas often show deviation from the regional geothermal gradient that increases towards the land surface in the top ∼100 m. This deviation is the sum of two effects: atmospheric global warming and urban heating. To invert the temperature profiles (T-logs), a novel analytical model is presented to distinguish effects of global warming and of urban structures on the ground thermal regime. The inversion is demonstrated on four characteristic T-logs measured in the city and suburbs of Zurich, Switzerland. The logging was performed in borehole heat exchanger U-tubes by an innovative, wireless measuring technique. Detailed information on past climatic and land use changes enabled the focus on two main urban heat sources, buildings and asphalt. For three of the locations, the T-logs could be reproduced with a plausible heating of the asphalt by 3–3.5 °C, and an average temperature of 15–16 °C below the basement of buildings. However, the other location within the highly urbanized area, is influenced by additional heat sources. In most of the cases, the increased subsurface temperatures and the associated stored additional geothermal energy, mainly originate from urban structures, while climate change is secondary.